REQUISITES OF TOTAL QUALITY MANAGEMENT IN TEACHER EDUCATION (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
With burgeoning growth of higher education sector in our country and global competition is increasing relentlessly, the need for improving quality of education and employability of our graduates has acquired a new urgency. The aim of this paper is improving the quality of higher education system to meet the demands of the society, quality of academic staff, infrastructure facilities and academic environment. This paper attempts to study the principles underlying total quality management in teacher education system.